1972
DOI: 10.1042/bj1280337
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the oestrogen sulphatase and arylsulphatase C activities of rat liver

Abstract: Detailed studies on the hydrolysis of p-acetylphenyl sulphate and oestrone sulphate by rat liver preparations strongly indicate that arylsulphatase C and oestrogen sulphatase are the same enzyme. Liver is the richest source of both enzymes, which have identical intracellular distributions, being localized mainly in the microsomal fraction. Low oestrogen sulphatase and arylsulphatase C activities were present in foetal liver and these increased at a similar rate after birth. The activities of the enzymes in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Of the three arylsulphatase enzymes (A, B, and C), arylsulphatase C has been suggested to be identical with oestrone sulphatase (2,5). This type of en zyme activity has been reported to be present in different mammalian tissues, e.g., liver (2,5), placenta (12), kidney (8), brain (10), and pituitary (13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the three arylsulphatase enzymes (A, B, and C), arylsulphatase C has been suggested to be identical with oestrone sulphatase (2,5). This type of en zyme activity has been reported to be present in different mammalian tissues, e.g., liver (2,5), placenta (12), kidney (8), brain (10), and pituitary (13).…”
Section: Resultsmentioning
confidence: 99%
“…Zuckerman and Hagerman (8) used for their assays debris-free homogenates in 0.2 M sodium phosphate buffer, pH 8.0, obtained by centrifugation at 600 g for 10 min. On the other hand, the study of Dolly et al (2) was carried out in a crude whole tissue homogenate pre pared in ice-cold water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in vitro showed that both diethylstilboestrol monosulphate and diethylstilboestrol disulphate are desulphated by a rat liver microsomal enzyme, arylsulphatase C, which has been shown to be identical with oestrogen sulphatase (Dolly et al, 1972). Presumably desulphation of diethylstilboestrol disulphate occurs in the liver to yield the monosulphate derivative, which has a free hydroxyl group available for conjugation with glucuronic acid.…”
Section: Experiments With Diethylstilboestrolmono[35s]sulphatementioning
confidence: 99%
“…The aim of this study was to determine intra-tumoural oestrone sulphatase activity in NMU-induced mammary tumours that regress with endocrine manipulation and in tumours which progress under oestrogenic stimulation. Previously, the rat and human oestrone sulphatase have been shown to be membrane-bound (Kawano et al, 1989;MacIndoe et al, 1988;Dolly et al, 1972) In both experiments the tumours and liver were harvested from all rats, immediately frozen in liquid nitrogen and stored at -70C. Tumour volumes were calculated using the formula in (d, x d2) i Tissue preparation All procedures were carried out at 0-4°C.…”
mentioning
confidence: 99%